(-2又六分之一)+5又十一分之一+(-4又六分之五)+(-25又十一分之一)

2025-02-25 17:21:44
推荐回答(4个)
回答1:

(-2又六分之一)+5又十一分之一+(-4又六分之五)+(-25又十一分之一)
=(-2又1/6-4又5/6)+(5又1/11-25又1/11)
=-7-20
=-27

(-3)+(+17)+(-6)+(+3)
=(3-3)+(17-6)
=0+11
=11

(+十七分之十三)+(-3.5)+(+十七分之四)+(+2.5)
=(2.5-3.5)+(13/17+4/17)
=-1+1
=0

回答2:

(-2又六分之一)+5又十一分之一+(-4又六分之五)+(-25又十一分之一)
=(-2又六分之一)+(-4又六分之五)+5又十一分之一)+(-25又十一分之一)
=-7-20=-27
(-3)+(+17)+(-6)+(+3)

=(-3)+(+3)+(+17)+(-6)
=17-6=11
(+十七分之十三)+(-3.5)+(+十七分之四)+(+2.5)
=(+十七分之十三)+(+十七分之四)+(-3.5)+(+2.5)
=1+2.5-3.5=0

回答3:

4554

回答4:

11